PENGARUH BUZZ MARKETING, EMOTIONAL BRANDING, CUSTOMER EXPERIENCE, DAN REVIEWS TERHADAP KEPUTUSAN PEMBELIAN TIKTOK SHOP SEMARANG - Yuni Nur Maulida; Yohan Wismantoro; Roymon Panjaitan; Pradana Jati Kusuma (Jurnal Economic Resource, 2026)
The development of social commerce through the TikTok Shop platform has changed the way consumers make online purchasing decisions, where these decisions are influenced not only by needs but also by social factors, emotional connections, user experience, and information from other consumers. This study aims to analyze and determine the extent of the influence of these four variables, both partially and simultaneously, on the purchasing decisions of TikTok Shop users in Semarang City. This is evidenced by the results of the t-test, where all variables have a t-value greater than the t-table value (1.971) and a significance level of 0.000 < 0.05, with Online Customer Reviews as the most dominant variable. These findings confirm that consumer purchasing decisions on TikTok Shop are influenced by exposure to viral information, emotional brand awareness, a pleasant shopping experience, and trust built through reviews from other customers.